The 1/N expansion of the symmetric traceless and the antisymmetric tensor models in rank three - Benedetti, Dario; Carrozza, Sylvain; Gurǎu, Rǎzvan; Kolanowski, Maciej (Communications in mathematical physics, 2019)
We prove rigorously that the symmetric traceless and the antisymmetric tensor models in rank three with tetrahedral interaction admit a 1 / N expansion, and that at leading order they are dominated by melon diagrams. This proves the recent conjecture of Klebanov and Tarnopolsky (JHEP 10:037, 2017. arXiv:1706.00839), which they checked numerically up to 8th order in the coupling constant.